Role of paliperidone extended-release in treatment of schizoaffective disorder - Carla M Canuso (Dove Medical Press, 2010)
Carla M Canuso1, Ibrahim Turkoz2, Dong Jing Fu3, Cynthia A Bossie31External Innovation Neuroscience Therapeutic Area, 2Biostatistics, Johnson & Johnson Pharmaceutical Research and Development, LLC, Titusville, NJ, USA; 3CNS Medical Affairs, Ortho-McNeil Janssen Scientific Affairs, LLC, Titusville, NJ, USAAbstract: Schizoaffective disorder is characterized by the presence of symptoms of both schizophrenia and a major mood disorder. The coexistence of these symptoms can be difficult to manage, and these patients are generally treated with antipsychotics as well as mood stabilizers and/or antidepressants. Additionally, no established treatment guidelines exist for this disorder. This review describes the combined results of two international, double-blind, placebo-controlled clinical studies of paliperidone extended-release (ER), an atypical antipsychotic recently approved in the US for the treatment of schizoaffective disorder. Subjects in these six-week trials were aged 18–65 years, had a diagnosis of schizoaffective disorder based on the Structural Clinical Interview for DSM-IV (Diagnostic and Statistical Manual of Mental Disorders, 4th Edition) Disorders, and were experiencing an acute exacerbation. The subjects from these studies had significant symptomatology as evidenced by a mean (standard deviation) baseline Positive and Negative Syndrome Scale total score of 92.8 (13.0). Based on Young Mania Rating Scale and/or a 21-item Hamilton Rating Scale for Depression score of ≥16 at baseline, 79.5% and 66.9% of subjects presented with prominent manic and depressive symptoms, respectively, and 46.4% presented with mixed symptoms. Approximately half (45%) of subjects were taking adjunctive mood stabilizers and/or antidepressants. Paliperidone ER was found to be effective in improving psychotic and mood symptoms in these subjects. Paliperidone ER was also effective as monotherapy or adjunctive to mood stabilizers and/or antidepressants for subjects with prominent manic, depressive, or mixed symptoms at baseline. No new tolerability signals were observed in this population. To the best of our awareness, these pooled data provide the largest data set of patients with schizoaffective disorder, and extend our knowledge of disease characteristics and treatment response.Keywords: paliperidone extended-release, antipsychotic, schizoaffective disorder